West Pacific Earthquake Forecasting Using NOAA Electron Bursts With Independent L-Shells and Ground-Based Magnetic Correlations - Fidani, Cristiano (Frontiers in Earth Science, 2021)
Recent advances in statistical correlations between strong earthquakes and several non-seismic phenomena have opened the possibility of formulating warnings within days or even hours. The retrieved correlations have been discovered for those ionospheric physical observations which lasted a long time, and realized by the same instruments, including multi-satellite recordings. One of those regarded the electron burst phenomena detected by NOAA, for which the conditional probability of a seismic event iwas calculated. Then an earthquake probability greater than its frequency was assigned when a satellite realized such a phenomenological observation. This approach refers to the correlations obtained between high energy electrons detected by NOAA POES and strong Indonesian and the Philippine earthquakes. It is reformulated here to realize a test of earthquake forecasting. The fundamental step is obtained by using a unique electron L-shell interval of 1.21 ≤ L ≤ 1.31, which decouples the electron parameters from the earthquake parameters. Then, the optimized correlation was recalculated to be 1.5 - 3.5 hours early, between electron bursts and an increased number of seismic events with M ≥ 6, therein improving significance too. Moreover, this methodology is reconnected to the frequency theory, and to Molchan's error diagram, by the probability gain; where a comparison among significance of various methods is given. The previously proposed physical link between the crust and ionosphere by magnetic interaction, presumably operating 4 - 6 hours before strong earthquakes, is examined quantitatively on the basis of recent magnetic pulse measurements. Consequently, the probability gain of earthquake forecasting is hypothetically calculated for both the dependent measurements of electron bursts from NOAA satellites and possible ground based magnetic pulse detection. This method of combining probability gains for earthquake forecasting is general enough that it can be applied to any pair of observables from space and the ground.